DESIGN OF MAIN CIRCUIT CHANNEL SELECTION FILTER IN DIRECT CONVERSION RECEIVER WIMAX WITH VARIABLE BANDWIDTH - RACHMADIANTO (NIM 13203043), FAISAL
Wireless communication technology which has grown rapidly emerged many new telecommunication standards. There is popular issue about multi standard receiver from designers. Direct conversion receiver (DCR) that does not have intermediate frequency become a solution of multi standard receiver because its high integration and low power consumption. Multi standard receiver can be achieved if radio frequency front end components capable to adapt not only one standard. This research is design of channel selection filter focuses on main circuit with variable filter bandwidth. This filter is baseband low pass filter DCR which located between mixer output and analog to digital converter (ADC) input. It will be implemented on bipolar transistor array chip THAT 300 series based on IC concept. Second order Butterworth filter chosen to fulfill requirement of Worldwide Interoperability for Microwave Access (Wi-MAX) standard which has bandwidth filter vary from 1,75 MHz, 3,5 MHz, 5 MHz to 10 MHz. The design of Gm-C filter circuit consist of four operational transconductance amplifier (OTA). The OTA topology based on folded cascode configuration in bipolar technology. Parameters design of the research are variable need bandwidth filter, gain passband, signal to noise ratio (SNR), and third order input intercept point (IIP3). The simulation in Spice shows -0,13 dB gain passband, -0,845 dBm IIP3 value with variable bandwidth from 0,875 MHz to 5 MHz. SNR value depends on the modulation so it has four different values. BPSK modulation gives 13,95 dB, QPSK with 1/2 coding rate gives 16,95 dB, 16-QAM with 3/4 coding rate gives 27,75 dB and 64-QAM with 3/4 gives 31,95 dB.